2022
DOI: 10.1111/trf.16873
|View full text |Cite
|
Sign up to set email alerts
|

The genomic landscape of blood groups in Indigenous Australians in remote communities

Abstract: Background: Red blood cell (RBC) membrane-associated blood group systems are clinically significant. Alloimmunisation is a persistent risk associated with blood transfusion owing to the antigen polymorphisms among these RBCassociated blood groups. Next-generation sequencing (NGS) offers an opportunity to characterize the blood group variant profile of a given individual.Australia comprises a large multiethnic population where most blood donors are Caucasian and blood group variants remain poorly studied among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The period prevalence of RC alloantibodies, including clinically significant ones associated with haemolytic transfusion reactions and haemolytic disease of the fetus/newborn (e.g., Rhesus, Kell, and Duffy), was higher in First Nations patients compared with non-First Nations patients. Our findings with respect to Kell (K) alloantibodies in First Nations patients are congruent with earlier smaller studies, including recent whole-genome sequencing studies on the distribution of blood group antigen profiles in First Nations Tiwi (n = 457) and Western Desert (n = 72) First Nations peoples [ 15 , 25 ]. Both these genomic studies found K antigen virtually absent in First Nations peoples compared with its presence in 9.1% (K) of Australian blood donors.…”
Section: Discussionsupporting
confidence: 91%
“…The period prevalence of RC alloantibodies, including clinically significant ones associated with haemolytic transfusion reactions and haemolytic disease of the fetus/newborn (e.g., Rhesus, Kell, and Duffy), was higher in First Nations patients compared with non-First Nations patients. Our findings with respect to Kell (K) alloantibodies in First Nations patients are congruent with earlier smaller studies, including recent whole-genome sequencing studies on the distribution of blood group antigen profiles in First Nations Tiwi (n = 457) and Western Desert (n = 72) First Nations peoples [ 15 , 25 ]. Both these genomic studies found K antigen virtually absent in First Nations peoples compared with its presence in 9.1% (K) of Australian blood donors.…”
Section: Discussionsupporting
confidence: 91%
“…Our study focuses on characterizing the PGx profile of the founder Indigenous population. We and others have characterized the blood group profiles ( Jadhao et al, 2022 ), genetic susceptibility to chronic kidney disease ( Thomson et al, 2019 ) and a variant affecting platelet function ( Ningtyas et al, 2020 ) in this population. This study is the first to comprehensively investigate clinically actionable pharmacogenes in the Tiwi people, contributing novel, important findings and further validating the results of a previous attempt to characterise Tiwi PGx profiles ( Jaya Shankar et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We selected 19 genes with pharmacological relevance for this analysis and a set of bioinformatics tools to identify star alleles present in these 2021). A consensus set of star alleles, called in agreement with at least two tools per each gene, were identified through an ensemble genotyping approach for further downstream analysis (Twesigomwe et al, 2020), except ABCG2, RYR1 and CACNA1S which are only supported by PyPGx tool (Lee et al, 2022). Genes with known SVs such as large deletions, insertions, or hybrids (e.g., CYP2D6, CYP2B6, CYP4F2, and G6PD), were evaluated using Cyrius, PyPGx, and StellarPGx which have better capability to detect complex variants.…”
Section: Identification Of Star Allelesmentioning
confidence: 99%
See 1 more Smart Citation
“…While the importance of extensive blood group antigen characterization in larger populations has been previously highlighted, many isolated populations, including founder populations, remain overlooked [ 9 ]. Founder populations are populations with reduced genetic diversity and higher homozygosity, usually due to genetic bottlenecks associated with geographical and cultural isolation.…”
Section: Introductionmentioning
confidence: 99%